The Use of Sociodrama to Instill Noble Morals (Akhlâq al-Karîmah) in Adolescents - Yusuf, Muhammad; Muslimah, Muslimah; Surawan, Surawan (Asosiasi Mahasiswa Program Pascasarjana | Universitas Islam Darussalam (UID) | Islamic University of Darussalam | Ciamis | Jawa Barat, 2023)
This study is driven by the impact of globalization, which, although having great effects on human labor, also has detrimental effects on human behavior, particularly among teenagers. Teenagers appear to lack etiquette and exhibit moral decay, with an escalating engagement in diverse criminal activities and hedonistic lives. The objective of this study is to determine the methods for effectively cultivating virtuous moral principles using sociodrama. This study employs a qualitative methodology. The findings of this study encompass the thematic elements employed in the sociodrama approach, utilizing folk stories and fairy tales derived from indigenous societies. These narratives are imbued with moral teachings and possess a high degree of comprehensibility. The process of inculcating virtuous ethical principles through sociodrama is comprised of three distinct phases: preparation, execution, and conclusion.